How does hormonal contraception affect the developing human adolescent brain?. (October 2018) - Cahill, Larry
Abstract : After over 50 years of hormonal contraception (HC), we know essentially nothing about how it influences brain development during adolescence. This review highlights key findings concerning sex dependent brain maturation during adolescence, including aspects that appear to be sex hormone dependent, with the aim of promoting research into understanding how HC influences adolescent brain maturation.